The Role of The Use of Information Technology in Orderly Financial Administration and Tax Compliance in Digital Business - Linda Afriani; Ipik Permana; Dewi Muliasari; Uswatun Khasanah (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
This study aims to examine the role of information technology on financial administrative order and tax compliance. We collected data through a survey on 136 digital business or startups owners/financial managers in Malang. The results show that the use of information technology has a positive effect on financial administration order; financial administration order has a positive effect on tax compliance; and the use of information technology has a positive effect on tax compliance mediated by the financial administration order. This research contributes to the knowledge by determining the relationship between the use of information technology and financial administration order as well as tax compliance to increase tax revenue in Indonesia. The digital businesses or startups use technology to maintain businesses’ financial administration order and hence, make easier calculation of taxable amounts. This research implies that the easiness of taxes payment through the online tax administration.